Comparison of DIPSI and IADPSG criteria for diagnosis of gestational diabetes mellitus- a prospective study in a sub-urban multi-speciality hospital - Patil, Yogini; Thiyagarajan, Kamalpriya; Chaudhari, Vaishali; Shah, Kshama; Vijay, Ria (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Gestational diabetes mellitus (GDM) refers to any degree of glucose intolerance with onset or when it is first diagnosed during pregnancy. Gestational diabetes mellitus is found to adversely affect the maternal and perinatal outcomes. The extent of the risks associated with GDM and the prevalence rate of GDM depends on the diagnostic criteria used and ethnicity of the pregnant women. Hence in order to prevent the morbidities that could result due to GDM, it is crucial to diagnose and treat during the early stages. However, confusion pertaining to the detection and diagnosis of GDM still prevails due to applicability of various threshold guidelines for its diagnosis. Methods: The study was a prospective, single-center, randomized, controlled study conducted in the year 2021 at the department of obstetrics and gynaecology of Bhaktivedanta Hospital and Research Institute, Thane, India. The objective of the study was to evaluate the utility of IADPSG and DIPSI guidelines for screening and diagnosis of GDM at a tertiary care center. Results: The sensitivity and specificity of DIPSI and IADPSG were compared and their readings were evaluated. The results proved that DIPSI criteria was more sensitive as compared to IADPSG criteria. Conclusions: DIPSI is a non-fasting, fairly simple, single test method that is appropriate for low resource countries. The sensitivity of IADPSG criteria was shown to be slightly lower when compared with DIPSI criteria in the current study, despite the fact that they are universal criteria for screening and diagnosing GDM around the world. The only limitation was that it was a single center study.